Pengaruh Ukuran Perusahaan, Profitabilitas, Leverage, Efisiensi Biaya, Dan Umur Perusahaan Terhadap Islamic Social Reporting (ISR) Pada Perbankan Syariah Di Indonesia - Prasetyoningrum, Ari Kristin (IAIN Kudus, 2018)
Islamic Social Reporting (ISR) is one of the indices of social responsibility disclosure whose indicators refer to Islamic ethical principles. Islamic banking operates according to Islamic principles, so ISR disclosures in Islamic banking should be within the corridor of Islamic values. This study aims to identify the factors that affect the disclosure level of Islamic Social Reporting (ISR) in sharia banking in Indonesia. Factors studied in this study are company size, profitability, leverage, efficiency and age of the company. The result of the research shows that the factor of financial factor in this research is firm size (SIZE), Profitability (ROA), Leverage (DER) and Cost Efficiency (BOPO) proved not significant influence to ISR, while Company Age factor (AGE) is statistically proven significant effect on the ISR.